2001
DOI: 10.2307/3558420
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ultrastructure of leaf and calyx glands in Galphimia brasiliensis (Malpighiaceae)

Abstract: The present study describes the anatomical structure of calyx and leaf glands in Galphimia brasiliensis and analyzes the mechanism of secretion. The glands are marginal and suprabasal, cup-shaped, sessile, and scarcely visible with the naked eye. Light microscopy reveals the following features: a thin, smooth cuticle; unistratified secretory cells; subglandular parenchyma; and vascular bundle supply composed of phloem and xylem with abundant druses of calcium oxalate. Transmission electron microscopy reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 4 publications
7
34
2
3
Order By: Relevance
“…The morphoanatomical similarity and analogous position between EFNs and elaiophores in Malpighiaceae indicate that these two secretory structures are homologous (Anderson 1990). Although the leaf glands of Malpighiaceae have been described as EFNs because of the predominance of secretion rich in sugars (Anderson 1990;Possobom et al 2010), lipids were also identified in the secretion of leaf glands of Galphimia brasiliensis (Castro et al 2001). This evidence supports the hypothesis of homology between EFNs and elaiophores and the importance of these secretory structures to understanding aspects of the phylogenetic relationships of Malpighiaceae (Castro et al 2001).…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…The morphoanatomical similarity and analogous position between EFNs and elaiophores in Malpighiaceae indicate that these two secretory structures are homologous (Anderson 1990). Although the leaf glands of Malpighiaceae have been described as EFNs because of the predominance of secretion rich in sugars (Anderson 1990;Possobom et al 2010), lipids were also identified in the secretion of leaf glands of Galphimia brasiliensis (Castro et al 2001). This evidence supports the hypothesis of homology between EFNs and elaiophores and the importance of these secretory structures to understanding aspects of the phylogenetic relationships of Malpighiaceae (Castro et al 2001).…”
Section: Introductionsupporting
confidence: 75%
“…observed in other species of Malpighiaceae (Castro et al 2001;Machado et al 2008). The occurrence of eglandulated leaves and leaves with two to four pairs of glands in the basal third of leaf blade and petiole have been previously described for B. muricata (Gates 1982), but this was not exactly the pattern found in the present study.…”
Section: Lays Araújo Nery Milene Faria Vieira and Marília Contin Vencontrasting
confidence: 56%
See 3 more Smart Citations